PENDAMPINGAN PEMBUATAN BROS DARI KAIN FLANEL UNTUK MENUMBUHKAN EKONOMI KREATIF - Kurniawati, Aprilia Wahyu; Ratih, Ratih; Rochman, Abdul; Suliwati; Marfu’ah, Uliyatul (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
STAIMAS WONOGIRI Thematic KPM in Randubang Hamlet, Pare Village, Selogiri District, Wonogiri Regency is a form of community service activity. KPMT activities were carried out from 3 July 2023 to 15 August 2023. Activities consisted of core activities, village activities and additional activities. This article specifically discusses the activities of UMKM in Randubang Hamlet which aim to provide experience, training, and as a learning process for the Randubang community, especially housewives. Entrepreneurial activities in this day and age seem to be increasingly commonplace and many people want to start their own entrepreneurship or UMKM. Entrepreneurial trends have made the role of UMKM actors currently growing rapidly because they are felt to have many roles, including the people in Randubang Hamlet. The work program for making brooches from flannel was carried out by STAIMAS Thematic KPM students located in the hamlet. The holding of brooches-making training involves the community, namely the ladies of RT 1 and 2 RW 10 of Dusun Randubang which aims to improve the economy in the area. It is hoped that this activity will become one of the UMKM ideas for local residents, especially IRTs, to train the spirit of UMKM development and bring up their creative ideas. This training is perfect for mothers and even teenagers because this brooch can be developed as a small business and can be done at any time at home. The response of the residents to this activity program was very good, responsive, and enthusiastic.